Comparing the proportion of the language of use and usage in teachers with different professional experience - Michońska-Stadnik, Anna (Neofilolog, 2012)
Effective communication in the classroom has been the focus of interest of second language acquisition research for several decades. Widdowson’s (1978) contribution to classroom discourse studies made a significant im-pact on our understanding of the concepts of language usage and use, and their role in classroom interaction. It is claimed that both types of teacher language should be employed to cater for the effective development of conversational skills. It was observed in the past that usage expressions were more frequent as the focus of classroom interaction was on correct-ness and not on fluency. Nowadays more and more teachers feel the need to use English in the classroom for the purpose of authentic communica-tion with their learners. The research described in this paper investigates whether and to what extent Polish teachers of English with different teach-ing experience vary their language directed at students as regards its usage and use. The results of observations and the analysis of lesson transcripts reveal that, surprisingly enough, more experienced teachers resort more of-ten to language directed at correctness, and the language of use seems to be rather neglected. Some possible explanations of this phenomenon are pre-sented in the concluding part of this paper.